Sustainability of Slum Improvement Program in Bangladesh: An Approach of Capacity Building, Community Participation and Empowerment - Rahman, Mohammed Mahbubur (Journal of Bangladesh Institute of Planners, 2015)
Slums providing housing to 30-70% of urban population in many developing countries have grown dramatically. Governments with international assistance, despite improving tenure security, environment, income and resources in many of these, could not eradicate the problems. Benefits could not be sustained due to lack in institutional development, policy implementation, governance, participation etc. This is more evident in Bangladesh where about 10 million poor in its urban areas suffer from substandard housing. Initially acting as a ‘provider’, the government could achieve little in terms of effects and numbers, this made the approach unsustainable. Thereafter, it shifted to providing training, finance, assistance in education, health, capacity building and environmental improvements so that the slum-dwelling poor could be ‘enabled’ to make sustainable solutions to their housing problems. This paper discusses this changed approach, and evaluates the achievements and sustainability of the Slum Improvement Program undertaken in last quarter of a century. Thus it will provide an insight into the way housing of the urban poor in the developing countries should be approached. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 59-72